Job satisfaction among executives : case of Japanese electrical and electronic manufacturing companies, Malaysia - Abdul, Mohani; Ismail, Hashanah; Jaafar, Noor Ismail (2010)
This paper reports on responses by Malaysian executives from Japanese electrical and electronic manufacturing companies on the level of job satisfaction amongst executives in Selangor, Malaysia. 35.1% of the executives were found to be highly satisfied, 31.8% moderately satisfied and 33.1% dissatisfied with their jobs. The study finds that relationship between age groups, duration of service and gender versus job satisfaction are significant at 95 % confidence level. The older executives who have more work experience showed a higher level of job satisfaction compared to the younger executives. In terms of gender, male executives experienced a higher level of job satisfaction compared to female executives. This could be attributed to the Japanese work culture that emphasizes the seniority - merit wage/ promotion and masculinity work culture. We suggest that promotion and salary increment policy should be geared towards a performance based system thus creating a healthy competitive environment that promotes excellent performance.